Identification and Validation of an Immune Evasion Molecular Subgroup of Patients With Colon Cancer for Implications of Immunotherapy - Zhang, Hongbin; Hong, Zaifa; Li, Peipei; Jiang, Han; Wu, Pengfei; Chen, Jinzhong (Frontiers in Genetics, 2022)
Immune evasion plays a critical role in the development and progression of colon cancer. However, studies to predict the prognosis of colon cancer via immune evasion (IEV)-related genes are limited. Therefore, on the basis of the 182 IEV-related genes, we used the univariate and lasso Cox regression model to construct the immune evasion related genes signature (IEVSig) of 16 prognostic IEV-related genes using the GEO and TCGA online databases. We found that IEVSig was an independent prognostic factor, and patients with high IEVSig had higher TNM stages and shorter recurrence-free survival than their counterparts. Kyoto Encyclopedia of Genes and Genomes and gene set enrichment analyses revealed that patients with high and low IEVSig had significantly different enrichment pathways. Immune cell infiltration analysis showed that nine immune cells obviously increased in the high IEVSig group, whereas five immune cells increased in the low IEVSig group. Immunotherapy cohort analysis revealed that patients with high IEVSig had a higher proportion of progressive disease or stable disease after receiving immunotherapy than patients with low IEVSig. Furthermore, patients with low IEVSig had higher tumor mutation load and neoantigen burden, which indicated an improved response to immunotherapy, than patients with high IEVSig. Thus, an IEV-related prognostic signature was established to predict the prognosis of patients with colon cancer and derive a prediction marker to offer insights into therapeutic strategies.